Affective intimacies - Kolehmainen, Marjo; Lahti, Annukka; Lahad, Kinneret (Manchester University Press, 2022)
This volume provides a novel platform to re-evaluate the notion of open-ended intimacies through the lens of affect theories. Contributors address the embodied, affective and psychic, sensorial and embodied aspects of their ongoing intimate entanglements across various timely phenomena. This fascinating collection asks how the study of affect enables us to rethink intimacies, what affect theories can do to the prevailing notion of intimacy and how they renew and enrich theories of intimacy in a manner which also considers its normative and violent forms. This collection brings together a selection of original chapters which invite readers to rethink such concepts as care, closeness and connectivity through the notion of affective intimacies. Based on rigorous research, it offers novel insights on a variety of themes from austerity culture to online discussions on regretting motherhood, from anti-ableist notions of health to teletherapies in the era of COVID-19, and from queer intimacies to critiques of empathy. Lively and thought-provoking, this collection contributes to timely topics across the social sciences, representing multiple disciplines from gender studies, sociology and cultural studies to anthropology and queer studies. By so doing, it advances the value of interdisciplinary perspectives and creative methodologies for understanding affective intimacies.